(untitled) (MAUSAM, 1961)
The paper describes a method of frequency modulating a 400ms/s U.H.F. transmitter by utilising the ionissing properties of a neon tubeto change the terminating impedance of a transmission line (tank circuit) periodically. With this method a 400 ms/s transmitter can be used for both radiosonde and radio-wind-finding work. The paper also describes how the method has been adopted to telemeter radiosonde data. Brief description of the relay circuits and changes in the design of radio-theodolite receiver (ground equipment for radio-wind-finding) for recording the data are given.